Identidade de gênero em situação de brinquedo: um estudo com crianças pré-escolares - Cunha, Elianne Madza de Almeida (2008)
The differences related to genders male and female are unquestionably presents in our society, where is always possible realize examples of how genders are presented distinctly or even oppositely about physical characteristics, expectation of behavior, social roles and task divisions. Therefore, the education of boys and girls differ much early, and it is due to the children assimilate the informations regarding their gender, construct significances and organize them in order to behave as a competent member of their culture. This study analyzes schoolchild manifestations of gender identity. The objective was verify how the child perceives his or her participation in a gender category, and how expresses this condition through games and manipulation of typical toys to boys and girls. 18 children (9 boys and 9 girls) took part in this study, aged between 4 years and 10 months and 5 years and 11 months of low social and economic levels. The children were filmed in trios, and there also were 10 available toys to them 5 typical boys toys and 5 typical girls toys. The preferential choices and the time of manipulation were analyzed. The results suggest that boys and girls tend to choose and manipulate mainly the toys that are culturally considered to each gender